Peningkatan Hasil Belajar Siswa pada Pembelajaran Tematik Terpadu Menggunakan Model Problem Based Learning (PBL) di Kelas IV Sekolah Dasar - Sovia Astari; Tin Indrawati (e-Journal Inovasi Pembelajaran Sekolah Dasar, 2019)
The purpose of this research is to describe the improvement student learning outcomes of integrated thematic learning by using Problem Based learning model at Grade IV SDN 05 Puhun Pintu Kabun Bukittinggi city. Type of the research is classroom action research  by using qualitative and quantitative approach. The subjects of the research were teacher and 27 grade IV students. Therefore, the Problem Based Learning model could improve the students learning outcomes of integrated thematic learning. The results of lesson plan observation on cycle I was 80.55%, and cycle II was 94.44%. The observation of teacher on cycle I was 79,69% and cycle II was 90.63%. While, the improvement of students aspect on cycle I was 76,58% and cycle II was 90,63%. While the average student learning outcomes in the knowledge aspect is 75.87 to 88.62, and in the skill aspect it gets an average of 83.33 to 92.21